Directionally tailoring the macroscopic polarization of piezocatalysis for hollow zinc sulfide on dual-doped graphene. (October 2021) - Pan, Meilan; Liu, Subiao; Pan, Bingjun; Chew, Jia Wei
Abstract: Inefficient mechanical energy capture and inadequate active sites of piezoelectric materials remain the principal impediment for more widespread application in environmental remediation. Herein, a strategy was proposed to substantially improve the piezocatalytic performance via hybridizing hollow wurtzite ZnS nanospheres (H-ZnS) onto flexible S, N-codoped graphene (SNG). The resulting piezoelectric composite (H-ZnS@SNG) exhibited faster electrical transport and more superior piezocatalytic properties for dye degradation (~100% in 10 min) under external strain (either ultrasonic or mechanical stirring), compared with bulk H-ZnS (~58.4%) and the piezoelectric composite coupled with solid wurtzite ZnS nanospheres (S-ZnS@SNG, ~89.9%). This improvement is ascribed to the strain-induced piezopolarization charges of H-ZnS@SNG, with the unique hollow structure of the H-ZnS nanosphere accelerating the electron transfer of heterogeneous graphene. H-ZnS@SNG had the optimum crystal phase and morphology of H-ZnS at the annealing treatment temperature of 700 ℃, leading to the highest piezocatalytic performance. Simulations of the wurtzite hollow ZnS piezocatalyst ties the enhanced performance to excellent flexibility, along with more catalytic active sites on both inner and outer surfaces, compared with solid ZnS. This study provides valuable insights into the mechanisms underlying the excellent purification efficiency by hollow structural piezocatalysts, which are expected to be useful in customizing the designs of such materials for practical implementation. Graphical Abstract: ga1 Highlights: Hollow structural H-ZnS@SNG fabricated by in-situ growth of hollow ZnS on graphene. H-ZnS@SNG gave 100% removal, relative to 58% by H-ZnS and 90% by S-ZnS@SNG. Hollow H-ZnS nanosphere enhanced electron transfer of heterogeneous graphene. Optimum crystal phase and morphology of H-ZnS at annealing temperature of 700 ℃. Simulations show hollow ZnS has excellent flexibility and more active sites.